2021
DOI: 10.1021/acs.jpcc.0c10095
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation-Induced Oxidation, Doping, and Etching of Two-Dimensional MoS2 Crystals

Abstract: Two-dimensional (2D) MoS 2 is a promising material for future electronic and optoelectronic applications. 2D MoS 2 devices have been shown to perform reliably under irradiation conditions relevant for a low Earth orbit. However, a systematic investigation of the stability of 2D MoS 2 crystals under high-dose gamma irradiation is still missing. In this work, absorbed doses of up to 1000 kGy are administered to 2D MoS 2 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 78 publications
(142 reference statements)
1
22
0
Order By: Relevance
“…Raman spectra (Figure b) of FGT present three main vibration peaks (E 2g 1 , E 2g 2 , and A 1g 1 ). , FGT nanoflakes mainly vibrate as in-plane vibrations of the Fe, Ge, and Te ions (E 2g 2 ), rather than in-layer reverse mode (E 2g 1 ) like FGT crystals. The blue shift of the E 2g mode after exfoliation is similar to that of other 2D materials, , which is due to the increase of surface force constant arising from the slight charge redistribution with the reduction of adjacent layers . The out-of-plane vibration mode A 1g 1 is also sensitive to the number of layers, and shows a red-shift phenomenon because of the decrease of the effective restoring force caused by the weakening of the vdW forces between adjacent layers .…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Raman spectra (Figure b) of FGT present three main vibration peaks (E 2g 1 , E 2g 2 , and A 1g 1 ). , FGT nanoflakes mainly vibrate as in-plane vibrations of the Fe, Ge, and Te ions (E 2g 2 ), rather than in-layer reverse mode (E 2g 1 ) like FGT crystals. The blue shift of the E 2g mode after exfoliation is similar to that of other 2D materials, , which is due to the increase of surface force constant arising from the slight charge redistribution with the reduction of adjacent layers . The out-of-plane vibration mode A 1g 1 is also sensitive to the number of layers, and shows a red-shift phenomenon because of the decrease of the effective restoring force caused by the weakening of the vdW forces between adjacent layers .…”
Section: Resultssupporting
confidence: 67%
“…The blue shift of the E 2g mode after exfoliation is similar to that of other 2D materials, 74,75 which is due to the increase of surface force constant arising from the slight charge redistribution with the reduction of adjacent layers. 76 The out-of-plane vibration mode A 1g 1 is also sensitive to the number of layers, and shows a red-shift phenomenon because of the decrease of the effective restoring force caused by the weakening of the vdW forces between adjacent layers. 77 Clean and clear nanoflakes are observed by an optical microscope (OM) (Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…5D). 115,116 Through a polymethyl methacrylate-assisted transfer, a single-layered MoS 2 nanosheet was transferred onto carbon grids. Atomic vacancy defects on the nanosheet were introduced by the Ga + ion irradiation using a focused ion beam.…”
Section: Heavy Ion Irradiationmentioning
confidence: 99%
“…Extensive investigations have been carried out to demonstrate the effects of exposure to deep ultraviolet light, neutron, electron, , proton, , and gamma-ray irradiation , on the electronic and optical properties of TMDs. However, only a few studies have evaluated irradiation-induced magnetism in TMDs. − Mathew et al observed that proton irradiated (2 MeV) MoS 2 flakes (200 ÎŒm) exhibited a ferrimagnetic behavior, and its origin has been explained based on vacancy clusters, isolated vacancies, and the formation of edge structures .…”
Section: Introductionmentioning
confidence: 99%